Fundamentals of General Surgery (Springer International Publishing, 2018)
This book provides a comprehensive guide to the surgical skills required during general surgery. General Concepts are covered with descriptions of basic terminology, the logic behind specific approaches, limitations of specific skills, technical and practical considerations, and safety of using specific approaches and skills. More advanced topics including gastro-intestinal anastomosis, exploring a patient after a major trauma, and managing crisis situations are also discussed, as well as current controversies and future directions within general surgery. Fundamentals of General Surgery is relevant to trainees in general surgery and its subspecialties, and aims to give them an easy to access resource that contains real life examples, iconography, and recommended further reading. .